2018
DOI: 10.1161/circresaha.117.312418
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Calcification by Growth Hormone–Releasing Hormone and Its Agonists

Abstract: GHRH-A controls osteogenesis in smooth muscle cells by targeting cross talk between protein kinase A and nuclear factor κB (p65) and through the suppression of reactive oxygen species production that induces the gene and alkaline phosphatase. Inflammation-mediated osteogenesis is thereby blocked. GHRH-A may represent a new pharmacological strategy to regulate VC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 72 publications
(111 reference statements)
2
21
0
Order By: Relevance
“…Biological effects of highly active agonistic analogs of GHRH synthesized in our laboratory have been evaluated in a variety of tests (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These studies have demonstrated that the GHRH agonist of MR series, represented by MR409, exhibit promising effects on the repair of cardiac tissue in rodent and swine models, such as the improvement of the ejection fraction, the decrease of the infarct size in rats, and the reduction of myocardial infarct scar in swine with subacute ischemic cardiomyopathy (9,17,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological effects of highly active agonistic analogs of GHRH synthesized in our laboratory have been evaluated in a variety of tests (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These studies have demonstrated that the GHRH agonist of MR series, represented by MR409, exhibit promising effects on the repair of cardiac tissue in rodent and swine models, such as the improvement of the ejection fraction, the decrease of the infarct size in rats, and the reduction of myocardial infarct scar in swine with subacute ischemic cardiomyopathy (9,17,29).…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, the GHRH agonist MR409 promoted survival of cardiac myocytes, reversed remodeling after myocardial infarction, attenuated cardiac hypertrophy, and improved heart function (9,17,21). The agonist MR409 also promoted the survival of pancreatic islets after transplantation, exerted protective effects in diabetic retinopathy, accelerated wound healing, and significantly impeded vascular calcification (14,19,20). These findings provide valuable insights for using agonists of GHRH as potential tissue repair agents.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Numerous studies demonstrated that GHRH exerts a variety of bioactivities due to its wide distribution and autocrine/paracrine mechanisms 4,5 . Therefore, GHRH and its analogs, including tesamorelin, MR-409, JI-38, and MIA-690, have been developed as potential therapeutic agents to treat diabetes, cancers, and cardiovascular diseases [5][6][7][8][9] .…”
mentioning
confidence: 99%
“…Its expression was shown to be increased with age 36 . In animal studies, the OPG-knockout mice not only developed osteoporosis at an early age but also manifested increased apoptotic myocardial cells, cardiac eccentric hypertrophy, attenuated contractile function and artery calcification [37][38][39] . In clinical studies, serum OPG was demonstrated to be positively associated with BMD [40][41][42] , and its expression was reported to be increased in HF patients 43,44 .…”
Section: Discussionmentioning
confidence: 99%